ANALISIS HUBUNGAN KARAKTERISTIK PEKERJAAN DENGAN MOTIVASI INTRINSIK PENYIAR RADIO ELRIA BUANA JAMBI - Yeri Saputra (Jurnal Dinamika Manajemen, 2014)
The objective of this research are : Firstly : To knowing and analyzing work characteristic picture and intrinsic motivation of Elria Buana FM Jambi Radio announcer. Secondly : To analyzing work charecteristic Relationship significance as announce to intrinsic motivation of Elria Buana Jambi announcer . Thirdly :To analyzing which is more dominant among work characteristic to interinsik motivation of Elria buana Jambi Announcer. Method of survey which is used in this research that is deskriptif with correlation pearson product moment to know the relationship and significance value between work characteristic and intrinsic motivation of elria buana Jambi announcer. Result of from this research is found that work characteristic there is relationship of positive and significance between work characteristic and intrinsic motivation of elria buana fm jambi announcer. Assumed by this matter happened because five work characteristic factor according to Oldham and hackman there is one able to and if each other integrated as good will support intrinsic motivation of elria buana jambi announcer . Recomandation able to be passed to this research that is radio shall can balance between intrinsic motivation which owned by announcer with eksterinsic motivation from radio , so that broadcaster motivational level as a whole can increase ,what later ,then will influence the quality of the announcer’s ferformance and in the end will have an effect on also at quality of radio alone.